IMPLEMENTASI PANCASILA DAN SISTEM KESEJAHTERAAN SOSIAL DI INDONESIA (PERMASALAHAN DAN SOLUSI) - Salakory, David Marthen (JURNAL BADATI, 2024)
This research examines the implementation of Pancasila in Indonesia's social welfare system, focusing on achievement indicators in four main sectors: education, health, economy, and infrastructure. Using a qualitative approach with historical- descriptive analysis methods, this study analyzes data from various primary and secondary sources. The results show significant variations in achievement, with the education sector reaching 80%, health 70%, economy 60%, and infrastructure 50%. The education sector demonstrates success in expanding access and improving quality, marked by a reduction in dropout rates from 15.3% to 8.7%. The National Health Insurance Program has covered 223.1 million people, indicating significant progress in healthcare access. In the economic sector, the reduction in poverty rates from 13.1% to 9.8% and the Gini ratio from 0.41 to 0.38 reflects progress in economic equality. Infrastructure still faces the biggest challenges in implementation, despite improvements in access to clean water and electrification. This study recommends strengthening institutional systems, accelerating infrastructure development, and revitalizing the people's economy to enhance the effectiveness of Pancasila implementation in the social welfare system.